ESCRT Machinery Mediates Cytokinetic Abscission in the Unicellular Red Alga Cyanidioschyzon merolae - Yagisawa, Fumi; Fujiwara, Takayuki; Takemura, Tokiaki; Kobayashi, Yuki; Sumiya, Nobuko; Miyagishima, Shin-ya; Nakamura, Soichi; Imoto, Yuuta; Misumi, Osami; Tanaka, Kan; Kuroiwa, Haruko; Kuroiwa, Tsuneyoshi (Frontiers in Cell and Developmental Biology, 2020)
In many eukaryotes, cytokinesis proceeds in two successive steps: first, ingression of the cleavage furrow and second, abscission of the intercellular bridge. In animal cells, the actomyosin contractile ring is involved in the first step, while the endosomal sorting complex required for transport (ESCRT), which participates in various membrane fusion/fission events, mediates the second step. Intriguingly, in archaea, ESCRT is involved in cytokinesis, raising the hypothesis that the function of ESCRT in eukaryotic cytokinesis descended from the archaeal ancestor. In eukaryotes other than animals, the roles of ESCRT in cytokinesis have been poorly understood. To explore the primordial core mechanisms for eukaryotic cytokinesis, we investigated ESCRT functions in the unicellular red alga Cyanidioschyzon merolae that diverged early in eukaryotic evolution. C. merolae provides an excellent experimental system. The cell has a simple organelle composition. The genome (16.5 Mb, 5335 genes) has been completely sequenced, transformation methods are established, and the cell cycle is synchronized by a light and dark cycle. Similar to animal and fungal cells, C. merolae cells divide through furrowing at the division site followed by abscission of the intercellular bridge. However, they lack an actomyosin contractile ring. The proteins that comprise ESCRT-I–IV, the four subcomplexes of ESCRT, are partially conserved in C. merolae. Immunofluorescence of native or tagged proteins localized the homologs of the five ESCRT-III components [charged multivesicular body protein (CHMP) 1, 2, and 4–6], apoptosis-linked gene-2-interacting protein X (ALIX), the ESCRT-III adapter, and the main ESCRT-IV player vacuolar protein sorting (VPS) 4, to the intercellular bridge. In addition, ALIX was enriched around the cleavage furrow early in cytokinesis. When the ESCRT function was perturbed by expressing dominant-negative VPS4, cells with an elongated intercellular bridge accumulated, a phenotype resulting from abscission failure. Our results showed that ESCRT mediates cytokinetic abscission in C. merolae. The fact that ESCRT plays a role in cytokinesis in archaea, animals, and early diverged alga C. merolae supports the hypothesis that the function of ESCRT in cytokinesis descended from archaea to a common ancestor of eukaryotes.